2016
DOI: 10.1021/acs.langmuir.6b00181
|View full text |Cite
|
Sign up to set email alerts
|

Motion of Optically Heated Spheres at the Water–Air Interface

Abstract: A micrometer-sized spherical particle classically equilibrates at the water-air interface in partial wetting configuration, causing about no deformation to the interface. In condition of thermal equilibrium, the particle just undergoes faint Brownian motion, well visible under a microscope. We report experimental observations when the particle is made of a light-absorbing material and is heated up by a vertical laser beam. We show that, at small laser power, the particle is trapped in on-axis configuration, si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
46
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 45 publications
6
46
0
Order By: Relevance
“…Likewise, it has been shown that the height profile of nanometer-thin films can be controlled by light-induced temperature gradients [9]. Direct conversion of light into work has also been evidenced in the field of active matter: actuation of microfabricated rotors [10] and micron-sized spherical particles [11,12] at the liquid-air interface have been accomplished recently, confirming that thermocapillarity is a highly efficient mechanism for colloidal self-propulsion.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Likewise, it has been shown that the height profile of nanometer-thin films can be controlled by light-induced temperature gradients [9]. Direct conversion of light into work has also been evidenced in the field of active matter: actuation of microfabricated rotors [10] and micron-sized spherical particles [11,12] at the liquid-air interface have been accomplished recently, confirming that thermocapillarity is a highly efficient mechanism for colloidal self-propulsion.…”
Section: Introductionmentioning
confidence: 91%
“…In the present study, we consider the hydrodynamic response of a surfactant-laden interface to a thermocapillary flow. Although many experiments are performed with radially symmetric sources [11,[16][17][18][19], little is known regarding 3D axisymmetric geometry. Also, arbitrary liquid depths have not yet received much consideration.…”
Section: Introductionmentioning
confidence: 99%
“…The main results of the present paper concern the slip velocity along metal surfaces. Though local heating of gold structures is widely used for manipulating of particles and cells [2][3][4]6] or powering microswimmers [7][8][9][10][11], there is at present no systematic study of the creep flow along a conducting surface. Evidence for thermoelectric driving of hot silica particles with a granular gold cap, was reported by one recent experiment [9]: probing the particle's self-propulsion velocity in 10 mM solutions of NaCl, LiCl and NaOH, revealed a saltspecific effect, which agrees qualitatively with the Seebeck coefficients of these electrolytes, S S S NaCl LiCl NaOH > > .…”
Section: Comparison With Experimentsmentioning
confidence: 99%
“…Laser-illuminated metal nanostructures provide versatile local heat engines [1], with optofluidic applications such as trapping of nanoobjects [2,3], manipulation of biological cells [4], microflows in capillaries [5], and colloidal assembly [6]. Similarly, thermally powered artificial microswimmers rely on the conversion of absorbed heat to motion; experimental realizations include metal-capped Janus particles that are driven by surface forces [7][8][9][10], and interface floaters that are advected by their self-generated Marangoni flow [11,12]. Force-free localization and steering have been achieved by temporal [13]or spatial [14] modulation of the laser power.…”
Section: Introductionmentioning
confidence: 99%
“…Laser-heated metal or carbon nanostructures provide versatile local heat sources, with applications ranging from photothermal imaging [1] to thermally powered artificial microswimmers [2]. The latter rely on the conversion of heat tomotion; experimental realizations include Janus colloids driven by surface forces [3], and interfacial particles that are advected by their self-generated Marangoni flow [4,5]. Force-free localization and steering have been achieved by temporal [6] or spatial [7] modulation of the laser power.…”
Section: Introductionmentioning
confidence: 99%